2007
DOI: 10.1016/j.infbeh.2006.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The association between prenatal exposure to cigarettes and infant and maternal negative affect

Abstract: This study examined the association between prenatal exposure to cigarettes and infant and maternal negative affect. Participants were 115 mother-infant dyads (69 prenatally exposed to cigarettes and 46 nonexposed). Infant and maternal negative affect were both assessed during the neonatal period (2-4 weeks of age) and again at 7 months of infant age. Results indicated that only prenatal exposure to cigarettes predicted infant negative affect. Infants who were prenatally exposed to more cigarettes had higher l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 65 publications
1
24
3
Order By: Relevance
“…Similarly, Leve et al (In Press) reported a negative zero-order association between maternal inhibition, an aspect of executive functioning, and toddler NE at 27 months of age. Although mechanisms of direct effects have not frequently been considered, two possibilities include prenatal (e.g., Schuetze & Rina, 2007) or genetic (e.g., Bell & Deater-Deckard, 2007) mechanisms. However, indirect, or mediated effects, wherein parental self-regulation influences aspects of the home environment, which subsequently act to influence children, represents another potential mechanism of influence.…”
Section: Maternal Self-regulation: Links With Infant Ne Home Chaos mentioning
confidence: 99%
“…Similarly, Leve et al (In Press) reported a negative zero-order association between maternal inhibition, an aspect of executive functioning, and toddler NE at 27 months of age. Although mechanisms of direct effects have not frequently been considered, two possibilities include prenatal (e.g., Schuetze & Rina, 2007) or genetic (e.g., Bell & Deater-Deckard, 2007) mechanisms. However, indirect, or mediated effects, wherein parental self-regulation influences aspects of the home environment, which subsequently act to influence children, represents another potential mechanism of influence.…”
Section: Maternal Self-regulation: Links With Infant Ne Home Chaos mentioning
confidence: 99%
“…2005a, 2005b; Muneoka et al, 1997; Slikker et al, 2005; Slotkin et al, 2006b, 2009a, 2009b; Slotkin and Seidler, 2005, 2010; Timofeeva et al, 2008; Xu et al, 2001). This may be an important contributor to the increased risk of depression associated with smoking or organophosphate exposure (Beseler et al, 2006, 2008; Chen et al, 2011; Goodman and Capitman, 2000; Jaga and Dharmani, 2007; Lee et al, 2007; Schuetze and Eiden, 2007; Upadhyaya et al, 2002; Wu and Anthony, 1999). Accordingly, in the current study, we examined whether prenatal exposure to nicotine alters the subsequent developmental neurotoxicity of chlorpyrifos directed toward 5HT synaptic function.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, self-reported prenatal smoking also has been associated with inattention, overactivity, and an impulsive response style at preschool and early school age (Day et al 2000; Fried, Watkinson, & Gray, 1992; Johnson, Vicary, Heist, & Corneal, 2001; Leech, Richardson, Goldschmidt, & Day, 1999), working memory and inhibition deficits in adolescents (Fried & Watkinson, 2001; Jacobsen, Slotkin, Westerveld, Mencl, & Pugh, 2006; Bennett et al, 2009), and negative emotionality in infancy and young children (Fried & Makin, 1987; Wakschlag & Hans, 2002; Schuetze & Eiden, 2007; Kelmanson, Erman, & Litvina, 2002; Brook, Brook, & Whiteman, 2000; Willoughby, Greenberg, Blair, Stifter, & Family Life Investigative Group, 2007). Dose-response relations between prenatal tobacco exposure and these externalizing behaviors have been reported (e.g., Linnet et al, 2003; Williams et al, 1998, Day et al, 2000).…”
mentioning
confidence: 99%